2014
DOI: 10.1111/myc.12177
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattii VGII in a Plathymenia reticulata hollow in Cuiabá, Mato Grosso, Brazil

Abstract: Little is known about the ecology of agents of cryptococcosis in Mato Grosso, without any data regarding to the sources of both agents in the environment. This study aimed to investigate Cryptococcus gattii and Cryptococcus neoformans associated with decay in tree hollows within the urban area of three different cities of Mato Grosso. Seventy-two environmental samples collected from 72 living trees in the cities of Cuiabá, Várzea Grande and Chapada dos Guimarães were sampled and analysed. One tree (Plathymenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
4
16
1
1
Order By: Relevance
“…The genotype VGII (25/56, 44.6%) was the most frequently isolated, as reported previously [36][37][38][39][40][41][42], and in agreement with this work. Different results have been observed in southern Brazil, with Casali et al [18] reporting 11 isolates of C. gattii serotype B type VGIII among the clinical samples they studied.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The genotype VGII (25/56, 44.6%) was the most frequently isolated, as reported previously [36][37][38][39][40][41][42], and in agreement with this work. Different results have been observed in southern Brazil, with Casali et al [18] reporting 11 isolates of C. gattii serotype B type VGIII among the clinical samples they studied.…”
Section: Discussionsupporting
confidence: 80%
“…This outbreak indicated that exposure to environmental sources, such as trees and soil contaminated by this yeast, can lead to cryptococcosis infection in humans and animals [38,39,40]. In a study analyzing environmental samples in Cuiabá, MT, Anzai et al [41] also isolated the genotype C. gattii VGII, which is similar to that detected in the clinical isolates analyzed in this work.…”
Section: Discussionsupporting
confidence: 57%
“…Subsequent reports have shown that this association is not limited to Eucalyptus trees or a particular geographical area which contributed to a better understanding of the diversity of its natural sources that interestingly, do not include poultry manure . Early in this decade, the outbreak at the west coast of North America indicated a drastic change in the adaptation of this organism to other environments …”
Section: How Does the Infection Occur?contrasting
confidence: 84%
“…23,25,31,32 Early in this decade, the outbreak at the west coast of North America indicated a drastic change in the adaptation of this organism to other environments. 26,31,[33][34][35] Cuba is an archipelago located in the Caribbean Sea. The local climate is tropical with an average temperature of 23°C with abundant and varied flora and fauna.…”
Section: The Causative Agent Of Cryptococcosismentioning
confidence: 99%
“…C. gattii AFLP6/VGII was also isolated in a study analysing environmental samples from tree hollows in Cuiabá, MT, conducted by Anzai et al . .…”
Section: Discussionmentioning
confidence: 99%